Powder metallurgically manufactured cellular metals from carat gold alloys for decorative applications. Issue 2 (March 2018) - Andersen, Olaf; Göhler, Hartmut; Kostmann, Cris; Quadbeck, Peter; Diologent, Frédéric; Colas, Damien; Kieback, Bernd
Abstract : This paper explores the possibilities of producing visually attractive cellular gold structures via two different powder metallurgical approaches: sintering of loosely packed gold fibers and replication of polymeric templates. In the latter case, two different templates were used: reticulated polyurethane (PU) foam and expanded polystyrene (EPS) spheres which were coated with atomized gold powder. In contrast to the fiber route, replication techniques require an intermediate thermal treatment for the removal of the templates prior to sintering. Typical carat gold alloys lend themselves for supersolidus liquid phase sintering due to a sufficient difference between solidus and liquidus temperature. This approach was applied to all three manufacturing routes and rigid cellular gold structures were obtained successfully in all cases.